Peculiarities of personalized selection of antipsychotic drugs for schizophrenia treatment - O.O. Khaustova; A.E. Asanova; N.O. Dzeruzhynska; M.M. Matiash (Medičnì Perspektivi)
Determining the optimal antipsychotic drugs, its effective dose, duration of therapy, form, and route of administration play a key role in the treatment of schizophrenia. In addition, special attention should be paid to the effectiveness of using different forms of antipsychotic drugs, in particular, the orally disintegrating form as exemplified by olanzapine. To study the peculiarities of a personalized approach in the use of antipsychotic drugs to achieve more effective results in treating schizophrenia, a content analysis was conducted using Ukrainian and English-language publications for the past 15 years. The search was conducted using the PubMed and CrossRef databases. An important conclusion is that the optimal therapeutic formula or drug should be selected individually, considering the specific patient's clinical condition. However, the most important factor in achieving successful results is the individually selected form and dose of the antipsychotic drugs. In addition to the patient's mental state, the choice of antipsychotic therapy is influenced by the spectrum of side effects, individual sensitivity to the active substance, pharmacological history, economic factors, etc. This is especially true for patients with insufficient adherence to treatment, which can often arise due to the side effects of drugs. In this case, it is important to correctly select both the active substance and the appropriate route of administration. Personalized selection of antipsychotic drugs also involves dynamic monitoring of changes in the patient's clinical condition, allowing for timely diagnosis of drug side effects, dose adjustments, or changes in the route of administration. These measures help increase patient adherence to treatment and improve their health-related quality of life.